Economics Impact of Climate Change on Agriculture GDP in Bhutan: Empirical Evidence from ARDL Approach - Waiba, Sangay Phuntsho (PT Inovasi Pratama Internasional, 2023)
This paper examines the economic impacts of climate change on agriculture in Bhutan. It focuses on the significance of the agriculture sector in Bhutan and analyzes the economic effects of climate change using the Autoregressive Distributed Lag (ARDL) model. The dependent variable used in the ARDL model is agriculture GDP, while the independent variables are temperature and rainfall. The ARDL model is employed to assess the short-run and long-run economic impacts of climate change on agriculture. The results of the study indicate that the agriculture sector has consistently contributed the highest GDP from 2009 to 2020 in Bhutan. Additionally, it has provided the most significant employment opportunities compared to other sectors between 2009 and 2019. The ARDL model results demonstrate that in the short run, the coefficient for temperature is positive at 0.16, and the coefficient for rainfall is 0.5, indicating that climate change has a positive impact on agriculture GDP. However, in the long run, the ARDL model reveals a negative impact of climate change on agriculture GDP. The coefficient for temperature is -11.2, and for rainfall, it is -1.13. These findings underscore the urgent need for measures to address the challenges posed by climate change. The paper recommends raising awareness about climate-smart initiatives and programs among stakeholders. Additionally, training and the adoption of climate-resilient seeds and techniques are necessary to mitigate the adverse effects of climate change on the agriculture sector.